Analysis to study the relationship between the chemical characterization of beers and the content of alpha acids present in two cultivars of hops (Revista de Ciências Agroveterinárias, 2023)
Hops (Humulus lupulus L.) is a plant whose female inflorescence is used in the brewing industry to impart bitterness and aroma to the drink, and Brazil imports about 98% of this raw material. However, this plant has been gaining prominence in the country, directly influencing the quality characteristics of the final product. Thus, the aim of this study was to explore the relationship between the alpha acids content of two hop cultivars produced in Brazil and the United States. The work was developed at UDESC/CAV, in Lages/SC, in the year 2021. A standard Indian Pale Ale beer, with the same base recipe, was produced. Each treatment consisted of the addition of different hop cultivars (Comet and Fuggle) from two origins (Brazilian and American). The results confirm that the cultivars and the origin of the hops influence the chemical characteristics of the evaluated beers. The amount of total phenolic compounds, flavonoids and antioxidant activity of the beer produced with the Brazilian Fuggle cultivar was 6.5% (850.09 meq gallic acid L-1); 75.5% (95.07 meq quercetin L-1) and 13.8% (6890 mmol Trolox L-1) higher, respectively, in relation to beer produced with the same cultivar originating in the United States. There was an inverse correlation between the alpha acid content and the phenolic content and antioxidant capacity of the beers. The beers in which Brazilian Fuggle hops were used, with the lowest alpha acid content among those adopted, showed a greater positive association with the total polyphenol content, individuals and antioxidant capacity of the beers. In conclusion, the beers produced with the cultivar Fuggle Brasileiro have a greater concentration of antioxidant substances.
Keywords: craft beer, antioxidants, Humulus lupulus L., brazilian hops